Uncovering the structure of agreeableness from self‐report measures. Issue 5 (21st November 2017) - Crowe, Michael L.; Lynam, Donald R.; Miller, Joshua D.
Abstract: Objective: Although there are several models of the lower‐order structure of Agreeableness, empirically derived descriptions of this domain are largely nonexistent. We examined the factor structure of Agreeableness items from multiple scales in order to empirically determine the facet‐level structure of the domain. Method: Participants ( N = 1, 205; 73% female; 84% White; M age = 35.5, SD = 17.26) completed 131 items from 22 scales measuring Agreeableness. Results: A series of factor analyses was conducted on 104 items to identify factor emergence of the domain from a single factor to increasingly more specific factors. A five‐factor solution consisting of facets labeled Compassion, Morality, Trust, Affability, and Modesty was identified as most appropriate. Factors from all levels of the construct were compared to current measures of the domain as well as a number of criterion variables. The patterns of association with criterion variables at the lower level of the Agreeableness domain showed significant divergence. Conclusions: The current results highlight how specific Agreeableness traits unfold from broader to more specific facets and how these traits are represented in existing measures of this important domain.